Preparation method of high-nickel positive electrode material with hollow structure and high-nickel positive electrode material

Through the continuous two-step co-precipitation method and a specific calcination process, the problems of complex and high cost of hollow structure high nickel cathode materials in the prior art are solved, and the structural stability and electrochemical performance of the material are improved, which is suitable for large-scale industrial production.

CN119118225BActive Publication Date: 2025-03-14PINGGAO GRP ENERGY STORAGE TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411588276.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

In the prior art, the process of preparing hollow structure high-nickel cathode materials is complicated, has high cost, and is not suitable for large-scale industrial production.

Method used

The continuous two-step co-precipitation method and a specific calcination process are adopted to control the growth process and arrangement of precursors by regulating the reaction conditions and the selection of doped elements to ensure the formation of hollow structures and the uniform distribution of doped elements.

Benefits of technology

It simplifies the process flow, reduces the preparation cost, improves the structural stability and electrochemical properties of the material, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118225B_ABST
    Figure CN119118225B_ABST
Patent Text Reader

Abstract

The present invention relates to a preparation method of a high-nickel positive electrode material with a hollow structure and a high-nickel positive electrode material, belonging to the technical field of high-nickel positive electrode materials. A high-nickel positive electrode material precursor is prepared by a two-step coprecipitation method, the obtained high-nickel positive electrode material precursor is cleaned and dried, and the dried high-nickel positive electrode material precursor is mixed with LiOH·H2O and calcined to obtain a high-nickel positive electrode material. The present invention adopts a continuous two-step coprecipitation method and a specific calcination process, and controls the growth process and arrangement mode of the precursor by regulating the reaction conditions and doping elements to ensure the formation of a hollow structure and the uniform distribution of doping elements. It can be seen that the present invention can more accurately control the particle morphology, reduce the formation of microcracks, and thus improve the cycle stability of the high-nickel positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high-nickel positive electrode materials, and in particular relates to a preparation method of a high-nickel positive electrode material with a hollow structure and the high-nickel positive electrode material. Background Art

[0002] Compared with traditional fuel vehicles, electric vehicles have lower carbon emissions and environmental impacts, meet global requirements for environmental protection and sustainable development, and have become a development trend in today's automotive field.

[0003] As a key component of electric vehicles, lithium-ion batteries (LIBs) have played an important role in promoting the technological advancement and market penetration of electric vehicles. Lithium-ion batteries have the characteristics of high energy density, long cycle life, high charge and discharge efficiency, and light weight, which meet the vehicle's endurance, fast charging, and energy efficiency. With the increasing demand for higher power and longer life, the development of lithium-ion battery positive electrode materials with excellent performance has become the key to the advancement of battery technology. High-nickel ternary positive electrode materials (LiNi x Co y Mn 1-x-y O2, NCM, x ≥ 0.6) has attracted widespread attention due to its higher capacity and energy density.

[0004] High-nickel ternary cathode materials have a typical α-NaFeO2-type layered structure, belonging to the hexagonal system and R3m space point group. Traditional high-nickel materials are micron-sized spherical secondary particles formed by the agglomeration of nano-sized primary particles. The morphology of these particles directly affects the battery performance, including electrolyte permeability, ion transfer rate, surface reactivity, crystal structure stability, mechanical stability, etc. Therefore, the particle morphology design of high-nickel cathode materials has become one of the important strategies for optimizing the performance of lithium-ion batteries. By precisely controlling the shape, size and structure of the particles, higher energy density, better cycle stability and faster charge and discharge rates can be achieved, thereby promoting the further development and application of battery technology.

[0005] High-nickel cathode materials are prone to form microcracks due to stress accumulation during the cycle process, which further causes particle breakage, electrolyte side reactions and other phenomena, deteriorating the battery cycle performance. Morphology design is an important means to improve the mechanical stability of high-nickel cathode materials and alleviate the formation of microcracks.

[0006] At present, the particle morphology of high-nickel cathode materials is regulated at two levels: primary particles and secondary particles. At the primary particle level, the shape, size and arrangement of the particles are adjusted to improve the mechanical strength of the high-nickel cathode materials and reduce the formation of microcracks. However, primary particles have limited effects on relieving mechanical stress and reducing the formation of microcracks. For secondary particles, by controlling the agglomeration of primary particles, secondary particles with different structures are designed, such as core-shell structures, hollow structures, internal porous, flaky particles, etc. However, these particle designs have more stringent requirements on the synthesis process, which increases the preparation cost.

[0007] Among them, hollow structure high nickel cathode materials currently require complex synthesis processes and precise process control to be prepared, including template method, solvothermal method or chemical deposition method, etc. These methods not only increase the preparation cost, but also may lead to low yield and process complexity. Patent CN111916726A prepares hollow structure high nickel cathode materials, using sulfonated polystyrene spheres as templates, and needs to introduce MOF materials. The preparation process is complicated, the cost of raw materials is high, and it is not suitable for large-scale industrial production. Summary of the invention

[0008] The technical problem to be solved by the present invention is to provide a preparation method of a high-nickel positive electrode material with a hollow structure and a high-nickel positive electrode material.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high-nickel positive electrode material with a hollow structure, comprising the following steps:

[0010] S1. Prepare a transition metal salt (TM) solution, divide the TM solution into two parts, add a halogen (X) salt to one part, called the first solution, and add a high-valent cation (R) salt to the other part, called the second solution, and stir the first solution and the second solution evenly; prepare two mixed solutions of NaOH solution and ammonia water, one part is the third solution, and the other part is the fourth solution, the ammonia concentration in the third solution is less than the ammonia concentration in the fourth solution, and stir the third solution and the fourth solution evenly;

[0011] S2. A two-step coprecipitation method is used to prepare a high-nickel positive electrode material precursor. In the first step of the coprecipitation process, the first solution and the third solution are pumped into a reaction container to control the temperature and pH; in the second step of the coprecipitation process, the second solution and the fourth solution are pumped into the reaction container to control the temperature and pH to obtain a high-nickel positive electrode material precursor;

[0012] S3, washing and drying the high-nickel positive electrode material precursor obtained in step S2;

[0013] S4, the high nickel positive electrode material precursor (Ni x Co yMn 1-x-y After mixing (OH)2, x≥0.6) with a lithium source (LiOH·H2O) and calcining, a high-nickel positive electrode material is obtained.

[0014] Furthermore, the TM solution in step S1 includes nickel sulfate hexahydrate (NiSO4·6H2O), cobalt sulfate heptahydrate (CoSO4·7H2O) and manganese sulfate monohydrate (MnSO4·H2O).

[0015] Furthermore, in step S1, the concentration of the TM solution is 1-4 mol / L.

[0016] Furthermore, in step S1, the concentration of the NaOH solution is 2-8 mol / L.

[0017] Furthermore, in step S1, the concentration of the ammonia water is 2 to 10 mol / L.

[0018] Furthermore, in step S1, the halogen (X) in the halogen salt is one or more of F, Cl, Br, and I.

[0019] Further, in step S1, the high-valent cation (R) in the high-valent cation salt is W 6+ 、 5+ , Nb 5+ 、Mo 6+ One or more of the .

[0020] Furthermore, in step S2, the reaction vessel is a continuously stirred reactor placed in a constant temperature water bath at 45-70°C.

[0021] Further, in step S2, the feed rates of the first solution and the third solution, the second solution and the fourth solution are 200-500 mL / h.

[0022] Furthermore, in step S2, the pH value is controlled at 10.5 to 12.5.

[0023] Furthermore, in step S3, the high-nickel positive electrode material precursor is washed with deionized water for multiple times and then dried, the drying temperature is 80-100° C., and the drying time is 10-15 hours.

[0024] Further, in step S4, during the lithiation process, the high nickel cathode material precursor and LiOH·H2O are mixed in a molar ratio of 1:1.05.

[0025] Furthermore, in step S4, the calcination process adopts two-step calcination, the first stage calcination temperature is 400-600°C, sintering for 4-6 hours, and the second stage calcination temperature is 700-900°C, sintering for 12-18 hours. The calcination process is carried out under oxygen flow conditions and the temperature is increased at a rate of 2°C / min.

[0026] Another object of the present invention is to provide a high-nickel positive electrode material having a hollow structure obtained by a preparation method of a high-nickel positive electrode material.

[0027] Due to the adoption of the above technical solution, it can be seen that the present invention adopts a continuous two-step co-precipitation method and a specific calcination process, and controls the growth process and arrangement of the precursor by regulating the reaction conditions and the doping elements to ensure the formation of the hollow structure and the uniform distribution of the doping elements. Compared with the traditional single-step preparation method, the present invention can more accurately control the particle morphology, reduce the formation of microcracks, and thus improve the cycle stability of the high-nickel positive electrode material.

[0028] In the two-step coprecipitation method of the present invention, low-concentration ammonia water, relatively mild reaction temperature and high pH value are mainly used in the first step of precursor preparation, wherein the transition metal ion first coordinates with ammonia to form [M (NH3) n ] 2+ , then [M(NH3) n ] 2+ With OH - The reaction forms M(OH)2. During this reaction, low concentration ammonia and OH - The content helps to promote the anisotropic growth of precursor nanosheets during the reaction, and the loose agglomerated particles are aggregated under mild reaction conditions. Based on the loose agglomerated particles generated by the first step of coprecipitation, the second step of coprecipitation preparation can be carried out by simply replacing the reaction solution without precursor transfer. In the second step of coprecipitation, a higher concentration of ammonia water and a lower pH value are used. The higher ammonium nitrogen concentration and strong stirring accelerate the agglomeration by forming irregular spheres. The lower pH value and higher reaction temperature promote the rapid growth of the external structure and orderly and dense arrangement. The process differences of the continuous two-step coprecipitation method are used to regulate the looseness and growth mode of the corresponding precursors, thereby preparing a hollow structure.

[0029] At the same time, the present invention improves the structural stability of high nickel positive electrode materials by co-doping with anions and cations. - ) can stabilize the structure of high nickel cathode materials and prevent excessive loss of oxides; cation doping (such as Ta 5+) improves the mechanical strength and electrochemical stability of the high-nickel positive electrode material. In addition, the doping element is crucial in the two-step coprecipitation reaction of the present invention. The first step of the coprecipitation process mainly involves anion doping process, which will obtain a TM-F bond that is stronger than the TM-O bond. The bond with stronger bond energy will improve the stability of the high-nickel positive electrode material, inhibit the precipitation of lattice O, and enhance the safety of the high-nickel positive electrode material. However, the chemical bond with strong binding force will hinder the insertion and extraction of Li, so the capacity will decrease slightly. Due to the small size and high electronegativity of fluoride ions, it is easy to cause excessive local concentration in the actual doping process, forming an uneven doping area, which in turn affects the overall performance of the high-nickel positive electrode material. Therefore, in the coprecipitation reaction or high-temperature calcination process, the reaction conditions (such as temperature, time, pH value, etc.) need to be precisely controlled to avoid overreaction or decomposition of fluoride, which puts higher requirements on process control. Therefore, based on the above considerations, the anion doping process is mainly carried out in the first step of the coprecipitation process. Low concentration of ammonia water, relatively mild reaction temperature and high pH value help promote uniform doping of anions. In the second step of co-precipitation, cation doping is mainly used. Cation doping widens the distance between lithium layers to promote the transmission of lithium ions, inhibits the migration of nickel ions to the lithium layer, and reduces cation mixing to maintain structural stability. In addition, the introduction of metal cations in the second step of co-precipitation will strengthen the transition metal-oxygen bond, thereby further strengthening the stability of the outer layer structure and maintaining the effectiveness of the hollow structure during the cycle. It can be seen that the choice of doping elements is also closely related to the preparation process.

[0030] In summary, the beneficial effects of the present invention are:

[0031] (1) The present invention adopts a continuous two-step co-precipitation method, which does not require the introduction of complex template materials. The process is simpler and suitable for integrated industrial production. In addition, the present invention improves the structural stability and electrochemical properties of the material by introducing co-doping of Ta and F.

[0032] (2) The present invention utilizes the process differences of the continuous two-step co-precipitation method to regulate the looseness and growth mode of the corresponding precursors, thereby preparing a hollow structure. Not only does it form a stable hollow structure inside the material, but it also introduces a wider range of doping elements (such as Ta and F), thereby further improving the performance of high-nickel positive electrode materials.

[0033] (3) The high-nickel cathode material of the present invention has good structural stability: the hollow structure can effectively alleviate the mechanical stress caused by volume change during charging and discharging, reduce the formation and diffusion of microcracks, and thus alleviate the secondary particle pulverization of the high-nickel cathode material. Anion and cation co-doping can enhance the interaction between atoms, reduce oxygen release and inhibit cation mixing, further improving the overall structural stability of the high-nickel cathode material.

[0034] (4) The hollow structure inside the high-nickel positive electrode material of the present invention provides a larger specific surface area, accelerates the penetration of the electrolyte, helps to improve the reaction activity of the electrode, and speeds up the transfer rate of charges and ions, thereby improving the charge and discharge performance of the battery.

[0035] (5) The hollow structure of the high-nickel cathode material of the present invention is conducive to heat dissipation and reduces heat accumulation, thereby improving the thermal stability and safety of high-nickel cathode material lithium-ion batteries.

[0036] (6) The preparation method of the present invention is simple and does not require the introduction of additional reagents, thereby greatly saving the preparation cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The present invention will be described in detail below with reference to the accompanying drawings and in combination with examples, and the advantages and implementation methods of the present invention will become more obvious. The contents shown in the accompanying drawings are only used to explain the present invention and do not constitute any limitation to the present invention in any sense. In the accompanying drawings:

[0038] Figure 1 X-ray diffraction patterns of high-nickel positive electrode materials prepared in Examples 1 to 3 of the present invention.

[0039] Figure 2 This is a scanning electron microscope image of the high-nickel positive electrode material prepared in Example 1 of the present invention.

[0040] Figure 3 This is an energy dispersion spectrum surface scan energy spectrum of the high nickel positive electrode material prepared in Example 1 of the present invention.

[0041] Figure 4 This is a scanning electron microscope image of the cross section of the high-nickel positive electrode material prepared in Example 2 of the present invention.

[0042] Figure 5 This is an energy dispersion spectrum surface scan spectrum of the cross section of the high-nickel positive electrode material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0043] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the best embodiment.

[0044] A method for preparing a high-nickel positive electrode material with a hollow structure comprises the following steps:

[0045] S1. Prepare a transition metal salt (TM) solution, divide the TM solution into two parts, add a halogen (X) salt to one part, called the first solution, and add a high-valent cation (R) salt to the other part, called the second solution, and stir the first solution and the second solution evenly; prepare two mixed solutions of NaOH solution and ammonia water, one as the third solution and the other as the fourth solution, the ammonia concentration in the third solution is less than that in the fourth solution, and stir the third solution and the fourth solution evenly.

[0046] S2. A two-step co-precipitation method is used to prepare a high-nickel positive electrode material precursor. During the first step of the co-precipitation process, the first solution and the third solution are pumped into a reaction container to control the temperature and pH; during the second step of the co-precipitation process, the second solution and the fourth solution are pumped into the reaction container to control the temperature and pH to obtain a high-nickel positive electrode material precursor.

[0047] S3. Clean and dry the high-nickel positive electrode material precursor obtained in step S2.

[0048] S4, the high nickel positive electrode material precursor (Ni x Co y Mn 1-x-y After mixing (OH)2, x≥0.6) with a lithium source (LiOH·H2O) and calcining, a high-nickel positive electrode material is obtained.

[0049] The TM solution in step S1 includes nickel sulfate hexahydrate (NiSO4·6H2O), cobalt sulfate heptahydrate (CoSO4·7H2O) and manganese sulfate monohydrate (MnSO4·H2O).

[0050] Wherein, in step S1, the concentration of the TM solution is 1-4 mol / L, and the molar ratio is 6:2:2-9:0.5:0.5.

[0051] Wherein, in step S1, the concentration of the NaOH solution is 2-8 mol / L.

[0052] Wherein, in step S1, the concentration of the ammonia water is 2-10 mol / L.

[0053] Wherein, in step S1, the halogen (X) in the halogen salt is one or more of F, Cl, Br, and I.

[0054] Wherein, in step S1, the high-valent cation (R) in the high-valent cation salt is W 6+ 、 5+ , Nb 5+ 、Mo 6+ One or more of the .

[0055] Wherein, in step S2, the reaction container is a continuously stirred reactor, which is placed in a constant temperature water bath at 45-70°C.

[0056] Wherein, in step S2, the feed rates of the first solution and the third solution, the second solution and the fourth solution are 200-500 mL / h.

[0057] Wherein, in step S2, the pH value is controlled at 10.5-12.5.

[0058] Wherein, in step S2, N2 is introduced into the reaction container during the reaction process to exhaust the air in the reaction device.

[0059] Wherein, in step S3, the high-nickel positive electrode material precursor is washed with deionized water for multiple times and then dried, the drying temperature is 80-100° C., and the drying time is 10-15 hours.

[0060] Wherein, in step S4, during the lithiation process, the high nickel cathode material precursor and LiOH·H2O are mixed in a molar ratio of 1:1.05.

[0061] In step S4, the calcination process adopts two-step calcination, the first stage calcination temperature is 400-600°C, sintering for 4-6 hours; the second stage calcination temperature is 700-900°C, sintering for 12-18 hours. The calcination process is carried out under oxygen flow and the temperature is increased at a rate of 2°C / min.

[0062] Another object of the present invention is to provide a high-nickel positive electrode material having a hollow structure obtained by a preparation method of a high-nickel positive electrode material.

[0063] Embodiment 1:

[0064] A method for preparing a high-nickel positive electrode material with a hollow structure comprises the following steps:

[0065] S1. Prepare a TM solution with a total concentration of 2 mol / L, including NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O, wherein the molar ratio of NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O is 8:1:1. Divide the TM solution into two parts at a ratio of 1:4. Add NH4F (1% of the total molar amount of metal salts) to the part with a ratio of 1, which is called the first solution. Add tantalum sulfate (1% of the total molar amount of metal salts) to the part with a ratio of 4, which is called the second solution. Stir the first solution and the second solution evenly.

[0066] Prepare two mixed solutions of 4 mol / L NaOH solution and ammonia water, one containing 2 mol / L low-concentration ammonia water, called the third solution, and the other containing 6 mol / L high-concentration ammonia water, called the fourth solution. Stir the third solution and the fourth solution evenly.

[0067] S2. During the first step of co-precipitation, the first solution and the third solution are pumped into a continuously stirred reactor, and the water bath temperature is maintained at 45°C and the pH is 12; during the second step of co-precipitation, the second solution and the fourth solution are pumped into a continuously stirred reactor, and the water bath temperature is maintained at 55°C and the pH is 11 to obtain a high-nickel positive electrode material precursor.

[0068] S3. Wash the high-nickel positive electrode material precursor obtained in step S2 with deionized water several times and dry it in an oven at 80° C. for 12 h.

[0069] S4, the high nickel cathode material precursor dried in step S3 was mixed with LiOH·H2O at a molar ratio of 1:1.05, and calcined in two steps under oxygen conditions, the first step of calcination temperature was 500°C, sintering for 5h, the second step of calcination temperature was 800°C, sintering for 15h, and the heating rate was 2°C / min. The high nickel cathode material Li (Ni 0.8 Co 0.1 Mn 0.1 ) 0.98 Ta 0.01 O 1.99 F 0.01 .

[0070] like Figure 1 As shown, the high nickel positive electrode material obtained in Example 1 was characterized by X-ray diffraction (XRD), and the results showed that the obtained high nickel positive electrode material had an α-NaFeO2 type rock salt structure, an O3 type layered structure, and an R3m space group.

[0071] like Figure 2 and Figure 3 As shown, the high-nickel cathode material obtained in Example 1 was characterized. From the scanning electron microscope (SEM), it can be seen that the high-nickel material maintains a spherical shape with a particle size between 10-15μm (mostly 12μm). The primary particles are clearly visible and are about 500nm in size. From the energy dispersive spectroscopy (EDS) surface scan energy spectrum, it can be seen that F and Ta are successfully doped into the high-nickel material and are evenly distributed.

[0072] In order to test the electrochemical properties of the prepared high-nickel positive electrode material, pole pieces were prepared, batteries were assembled, and electrochemical performance tests were performed. First, a positive electrode pole piece was prepared. The high-nickel material, acetylene black, and polyvinylidene fluoride (PVDF) prepared in Example 1 were ground and mixed uniformly in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, coated on aluminum foil, and vacuum dried to form a circular pole piece. Then a button half-cell was assembled. The CR2025 button half-cell was assembled in an argon glove box. The negative electrode used was a lithium sheet, the diaphragm was a porous polypropylene film Celgard2400, and the electrolyte was a mixed solvent of 1 mol / L LiPF6 dissolved in dimethyl carbonate, diethyl carbonate, and ethyl carbonate (volume ratio of 1:1:1). Subsequently, an electrochemical performance test was performed. The LAND CT 2001A tester of Wuhan Landian Electronics Co., Ltd. was used to perform charge and discharge tests on the assembled battery, and the charge and discharge cut-off voltage was 2.8-4.3V (1C=190 mA g -1 ).

[0073] The high nickel cathode material obtained in Example 1 has an activation capacity of 210.7 mAh g at a rate of 0.1C in the first week. -1 The coulombic efficiency is 88.9%. The cycle performance test results show that the initial capacity at 1C rate is 190.4 mAh g -1 After 100 cycles, the capacity retention rate was 91.3%. In the rate performance test, the capacity of the high-nickel cathode material prepared at a high rate of 5C can still reach 160.2 mAh·g -1 The experimental results show that the hollow structure of high-nickel cathode materials formed by Ta and F doping has enhanced structural stability, can effectively alleviate the formation of microcracks, accelerate electrolyte penetration, and help improve the cycle stability and rate performance of the battery.

[0074] Embodiment 2:

[0075] A method for preparing a high-nickel positive electrode material with a hollow structure comprises the following steps:

[0076] S1. Prepare a TM solution with a total concentration of 2 mol / L, including NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O, wherein the molar ratio of NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O is 8:1:1. Divide the TM solution into two parts at a ratio of 1:4. Add NH4F (1% of the total molar amount of metal salts) to the part with a ratio of 1, which is called the first solution. Add ammonium metatungstate (2% of the total molar amount of metal salts) to the part with a ratio of 4, which is called the second solution. Stir the first solution and the second solution evenly.

[0077] Prepare two mixed solutions of 4 mol / L NaOH solution and ammonia water, one containing 3 mol / L low-concentration ammonia water, called the third solution, and the other containing 6 mol / L high-concentration ammonia water, called the fourth solution. Stir the third solution and the fourth solution evenly.

[0078] S2. During the first step of co-precipitation, the first solution and the third solution are pumped into a continuously stirred reactor, and the water bath temperature is maintained at 45°C and the pH is 12; during the second step of co-precipitation, the second solution and the fourth solution are pumped into a continuously stirred reactor, and the water bath temperature is maintained at 60°C and the pH is 11 to obtain a high-nickel positive electrode material precursor.

[0079] S3. Wash the high-nickel positive electrode material precursor obtained in step S2 with deionized water several times and dry it in an oven at 80° C. for 12 h.

[0080] S4, the high nickel cathode material precursor dried in step S3 was mixed with LiOH·H2O at a molar ratio of 1:1.05, and calcined in two steps under oxygen conditions, the first step of calcination temperature was 450°C, sintering for 5h, the second step of calcination temperature was 850°C, sintering for 13h, and the heating rate was 2°C / min. The high nickel cathode material Li(Ni 0.8 Co 0.1 Mn 0.1 ) 0.957 W 0.02 O 1.99 F 0.01 .

[0081] like Figure 1 As shown, the high nickel positive electrode material obtained in Example 2 was characterized by XRD, and the results showed that the obtained material had an α-NaFeO2 type rock salt structure, an O3 type layered structure, and an R3m space group.

[0082] like Figure 4 As shown, the high nickel cathode material obtained in Example 2 was characterized by cross-sectional scanning electron microscopy (SEM), confirming that the prepared high nickel cathode material had a hollow structure. In addition, the high nickel material maintained a good spherical shape, with a particle size of about 11 μm and a pore size of about 2 μm. The primary particles were clearly visible and distributed radially within the secondary particles. This structure has a beneficial effect on relieving mechanical stress, reducing microcrack extension and secondary particle pulverization.

[0083] The electrode sheet was prepared and the battery was assembled using the method of Example 1, and the electrochemical performance of the high-nickel positive electrode material obtained in Example 2 was tested. The activation capacity at 0.1C rate in the first week was 208.3 mAh·g -1 The coulombic efficiency is 88.2%. The cycle performance test results show that the initial capacity at 1C rate is 189.8 mAh g-1 After 100 cycles, the capacity retention rate was 92.6%. In the rate performance test, the capacity of the high nickel material prepared at a high rate of 5C can still reach 163.7 mAh g -1 . The experimental results show that the hollow structure of high-nickel cathode materials formed by W and F doping has enhanced structural stability, which helps to improve the cycle stability and rate performance of the battery. W doping enters the transition metal layer, and high-content W doping forms more strong WO bonds to improve the stability of the layered structure of high-nickel cathode materials during the cycle, inhibit the formation of irreversible phase change, slow down the formation of mechanical stress and microcracks, and improve the cycle stability of the battery.

[0084] Embodiment 3:

[0085] A method for preparing a high-nickel positive electrode material with a hollow structure comprises the following steps:

[0086] S1. Prepare a TM solution including NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O with a total concentration of 3 mol / L, wherein the molar ratio of NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O is 8:1:1. Divide the TM solution into two parts according to a ratio of 1:3, add NH4F to the part with a ratio of 1, which is called the first solution, and add molybdenum sulfate to the part with a ratio of 3, which is called the second solution. The first solution and the second solution are stirred evenly.

[0087] Prepare two mixed solutions of 6mol / L NaOH solution and ammonia water, one containing 3mol / L low-concentration ammonia water, called the third solution, and the other containing 8mol / L high-concentration ammonia water, called the fourth solution. Stir the third solution and the fourth solution evenly.

[0088] S2. During the first step of co-precipitation, the first solution and the third solution are pumped into a continuously stirred reactor, and the water bath temperature is maintained at 40°C and the pH is 11.5; during the second step of co-precipitation, the second solution and the fourth solution are pumped into a continuously stirred reactor, and the water bath temperature is maintained at 50°C and the pH is 10.5 to obtain a high-nickel positive electrode material precursor.

[0089] S3. Wash the high-nickel positive electrode material precursor obtained in step S2 with deionized water several times and dry it in an oven at 80° C. for 12 h.

[0090] S4, the high nickel cathode material precursor dried in step S3 was mixed with LiOH·H2O at a molar ratio of 1:1.05, and calcined in two steps under oxygen conditions, the first step calcination temperature was 550°C, sintering for 5h, the second step calcination temperature was 850°C, sintering for 12h, and the heating rate was 2°C / min. The high nickel cathode material Li(Ni 0.8 Co0.1 Mn 0.1 ) 0.973 Mo 0.01 O 1.98 F 0.02 .

[0091] like Figure 1 As shown, the high nickel positive electrode material obtained in Example 1 was characterized by X-ray diffraction (XRD), and the results showed that the obtained material had an α-NaFeO2 type rock salt structure, an O3 type layered structure, and an R3m space group.

[0092] like Figure 5 As shown, the high-nickel positive electrode material obtained in Example 3 was characterized by a cross-sectional energy dispersive spectroscopy (EDS) surface scanning energy spectrum. The results showed that the high-nickel positive electrode material maintained a good spherical shape and had a hollow structure, and the doped F and Mo elements were evenly distributed inside the particles.

[0093] The method of Example 1 was used to prepare the electrode sheet and assemble the battery, and the electrochemical performance of the high-nickel positive electrode material obtained in Example 3 was tested. The activation capacity at 0.1C rate in the first week was 205.6 mAh·g -1 The coulombic efficiency is 89.8%, indicating that a higher content of F anion doping helps to improve the first-cycle coulombic efficiency. The cycle performance test results show that the initial capacity at 1C rate is 188.6 mAh g -1 After 100 cycles, the capacity retention rate was 92%. In the rate performance test, the capacity of the high-nickel cathode material prepared at a high rate of 5C can still reach 161.9 mAh g -1 . The experimental results show that the hollow structure of high nickel cathode materials formed by Mo and F doping has enhanced structural stability, which helps to improve the cycle stability and rate performance of the battery. Since the electronegativity of F ions is stronger than that of O ions, the TM-F bond is more stable than the TM-O bond, which can effectively inhibit oxygen loss, enhance structural stability, and play a role in regulating the valence of elements.

[0094] Comparative Example 1:

[0095] The following steps are involved:

[0096] S1. Prepare a TM solution with a total concentration of 2 mol / L including NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O. The molar ratio of NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O is 8:1:1. Stir well.

[0097] Prepare a mixed solution of 4 mol / L NaOH solution and 2 mol / L ammonia water and stir evenly.

[0098] S2. Pump the TM solution and the alkali mixed solution into a continuously stirred reactor, maintain the water bath temperature at 45°C and the pH at 12, and obtain a high-nickel positive electrode material precursor.

[0099] S3. Wash the high-nickel positive electrode material precursor obtained in step S2 with deionized water several times and dry it in an oven at 80° C. for 12 h.

[0100] S4, the high nickel cathode material precursor dried in step S3 was mixed with LiOH·H2O at a molar ratio of 1:1.05, and calcined in two steps under oxygen conditions, the first step calcination temperature was 500°C, sintering for 5h, the second step calcination temperature was 800°C, sintering for 15h, and the heating rate was 2°C / min. The high nickel cathode material LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0101] The method of Example 1 was used to prepare the electrode sheet and assemble the battery, and the electrochemical performance of the high-nickel positive electrode material obtained in Comparative Example 1 was tested. The activation capacity at 0.1C rate in the first week was 197.9 mAh·g -1 The coulombic efficiency is 86.5%. The cycle performance test results show that the initial capacity at 1C rate is 181.3 mAh g -1 After 100 cycles, the capacity retention rate was 81.7%. In the rate performance test, the capacity of the high-nickel cathode material was 149.7 mAh g at a high rate of 5C. -1 .

[0102] Comparative Example 2:

[0103] The following steps are involved:

[0104] S1. Prepare 2 mol / L TM solution including NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O, with the molar ratio of NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O being 8:1:1, and stir evenly.

[0105] Prepare two mixed solutions of 4 mol / L NaOH solution and ammonia water, one containing 2 mol / L low-concentration ammonia water, called the third solution, and the other containing 6 mol / L high-concentration ammonia water, called the fourth solution. Stir the third solution and the fourth solution evenly.

[0106] S2. During the first step of co-precipitation, the TM solution and the third solution are pumped into a continuously stirred reactor, and the water bath temperature is maintained at 45°C and the pH is 12. During the second step of co-precipitation, the TM solution and the fourth solution are pumped into a continuously stirred reactor, and the water bath temperature is maintained at 55°C and the pH is 11 to obtain a high-nickel positive electrode material precursor.

[0107] S3. Wash the high-nickel positive electrode material precursor obtained in step S2 with deionized water several times and dry it in an oven at 80° C. for 12 h.

[0108] S4, the high nickel cathode material precursor dried in step S3 was mixed with LiOH·H2O at a molar ratio of 1:1.05, and calcined in two steps under oxygen conditions, the first step calcination temperature was 450°C, sintering for 5h, the second step calcination temperature was 850°C, sintering for 13h, and the heating rate was 2°C / min. The high nickel cathode material LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0109] The method of Example 1 was used to prepare the electrode sheet and assemble the battery, and the electrochemical performance of the high-nickel positive electrode material obtained in Comparative Example 2 was tested. The activation capacity at 0.1C rate in the first week was 198.5 mAh·g -1 The coulombic efficiency is 87.1%. The cycle performance test results show that the initial capacity at 1C rate is 183.6 mAh g -1 After 100 cycles, the capacity retention rate was 86.4%. In the rate performance test, the material capacity was 154.8 mAh g at a high rate of 5C. -1 .

[0110] The comparison of electrochemical performances of batteries assembled with the high nickel positive electrode materials prepared in Examples 1 to 3, Comparative Examples 1 and 2 is shown in Table 1.

[0111] Table 1 Electrochemical performance data of batteries assembled with high nickel positive electrode materials prepared in Examples 1 to 3, Comparative Examples 1 and 2

[0112]

[0113] It can be seen that the activation capacity at the first week 0.1C rate, the first week coulombic efficiency, the initial capacity at 1C rate, the capacity retention rate after 100 cycles, and the capacity of the high-nickel positive electrode material prepared at a high rate of 5C of Comparative Examples 1 and 2 are all lower than those of the embodiments of the present invention.

[0114] The embodiments of the present invention are described in detail above, but the contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing a high-nickel positive electrode material with a hollow structure, characterized in that: The following steps are involved: S1. Prepare a TM solution, divide the TM solution into two parts, add a halogen salt to one part, called the first solution, and add a high-valent cation salt to the other part, called the second solution, and stir the first solution and the second solution evenly; prepare two mixed solutions of NaOH solution and ammonia water, one part is the third solution, and the other part is the fourth solution, the ammonia concentration in the third solution is less than that in the fourth solution, and stir the third solution and the fourth solution evenly; S2. A two-step coprecipitation method is used to prepare a high-nickel positive electrode material precursor. In the first step of the coprecipitation process, the first solution and the third solution are pumped into a reaction container to control the temperature and pH; in the second step of the coprecipitation process, the second solution and the fourth solution are pumped into the reaction container to control the temperature and pH to obtain a high-nickel positive electrode material precursor; S3, washing and drying the high nickel positive electrode material precursor obtained in step S2; S4, mixing the high nickel positive electrode material precursor dried in step S3 with LiOH·H2O and calcining to obtain a high nickel positive electrode material; In step S1, the TM solution includes NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O; the concentration of the TM solution is 1-4 mol / L; the concentration of the NaOH solution is 2-8 mol / L; the concentration of the ammonia water is 2-10 mol / L; the halogen salt is NH4F; the high-valent cation in the high-valent cation salt is W 6+ 、 5+ , Nb 5+ 、Mo 6+ One or more of the following; In step S2, the reaction vessel is a continuously stirred reactor placed in a constant temperature water bath at 45-70°C; the pH value is controlled at 10.5-12.5; In step S2, the first step uses low-concentration ammonia water, a milder reaction temperature and a higher pH value; the second step uses higher-concentration ammonia water, a lower pH value and a higher reaction temperature.

2. The method for preparing a high-nickel positive electrode material with a hollow structure according to claim 1, characterized in that: In step S3, the high-nickel positive electrode material precursor is washed with deionized water and then dried at a drying temperature of 80 to 100° C. for a drying time of 10 to 15 hours.

3. The method for preparing a high-nickel positive electrode material with a hollow structure according to claim 1, characterized in that: In step S4, during the lithiation process, the high nickel cathode material precursor and LiOH·H2O are mixed in a molar ratio of 1:1.

05.

4. The method for preparing a high-nickel positive electrode material with a hollow structure according to claim 1, characterized in that: In step S4, the calcination process adopts a two-step calcination, the first stage calcination temperature is 400-600°C, and the sintering time is 4-6 hours; the second stage calcination temperature is 700-900°C, and the sintering time is 12-18 hours; the calcination process is carried out under oxygen conditions and the temperature is increased at a rate of 2°C / min.

5. Anion-cation co-doped high nickel positive electrode material with a hollow structure, characterized in that: The hollow structure high nickel positive electrode material is prepared by the preparation method of any one of claims 1 to 4.

Citation Information

Patent Citations

  • High-nickel cobalt-free positive electrode material and preparation method thereof

    CN111916726A

  • High-nickel positive electrode material with reconstructed primary particle surface layer and preparation method thereof

    CN111755692A

  • Lithium ion positive electrode material, lithium ion battery and preparation method

    CN118398806A